STUDENTS’ PERCEPTIONS OF DESIGN-BASED INTERACTIVE LEARNING TOOLS IN A CONSTRUCTIVIST-BASED LEARNING ENVIRONMENT: Received: 8th April 2021; Revised: 26th November 2021, 27th November 2021; Accepted: 1st December 2021 - Kwok, Wai Jing; Lim, Thian Li (PUPIL: International Journal of Teaching, Education and Learning, 2021)
In this 21st century, the development of technology has brought changes in many aspects of our life, especially brought huge impact in education sector. Research has shown that constructivist-based learning environment provide students with more active, engaging and problem-solving learning experiences. Interactive learning tools such as blog and Kahoot are able to provide more interactive, real time feedback, enhance communication and collaboration between teacher and students. This study investigates students’ perception of using interactive learning tools in a constructivist-based learning environment. Qualitative research approach was adopted to gauge the students’ attitudes and perceptions towards the use of blog and Kahoot in their learning process. The results of the study have shown that students have become active learners by actively participated in class activities. Apart from that, it has been found that students improve continuously, became independent learners, actively giving and receiving feedback from lecturer and classmates. The results of this study will bring benefits to lecturers and higher education institutions where they will understand the advantages of integrating interactive learning tools in the constructivist-based learning environment. Lecturers will need to design and impart skills and competences that employers need the most so that they can integrated in the curriculum.